IMPLEMENTASI MODEL PEMBELAJARAN ASYNCHRONOUS DALAM PERANCANGAN APLIKASI SIMULASI PANDUAN PECINTA ALAM BERBASIS ANDROID - Erlan Darmawan (Cloud Information, 2018)
Application Based Asynchronous Learning model is a self-learning model for the beginner of nature lovers who want to learn about the basic material about nature lovers, while the model of development using asynchronous learning models. Asynchronous learning is learning independently. Learners can interact with each other with material that has been provided at the time of their choosing. A discussion thread is an example of an asynchronous learning (5: Fajar Galuh Sujiatmoko: 2013). The operating system used for the development of applications is android operating system, Android is an operating system for mobile phones based on Linux. Android provides an open platform to developers for creating their own applications to be used by a variety of mobile devices (5: Eriza Siti Mulyani: 2012). In Additional  supporting softwares for application development are PHP and MySQL.The method used for the development of this application is RUP (Rational Unified Process). RUP is a software engineering process of defining the good (well defined) and structuring a good (well structured) (Rosa U.S. and Shalahudin M, 2011). By designing this application is expected to make easy in the learning process.